Analysis of Students’ Writing Ability through Diary Writing Habits at MIN 11 Medan City - Siti Nurhalizah; Safran Safran (MANAZHIM, 2023)
The essence of the problems in this study are: first, to determine the writing ability of students of class V MIN 11 Medan City. Second, to find out the teacher's strategy in improving students' writing skills through the habit of writing diaries in class V MIN 11 Medan City. Third, to find out the process of habituating the ability to write diaries in class V MIN 11 Medan City. This research is a qualitative research, which was conducted in class V MIN 11 Medan City, who acted as research subjects were students of class V MIN 11 Medan City, totaling 28 people. Data collection techniques in this study, namely observation, interviews, and documentation. Based on the findings and results of data analysis, it can be concluded that the habit of writing diaries in fifth grade students at MIN 11 Medan City has proven to have a positive impact on improving children's writing abilities when learning to write in Indonesian. The indicators that can be seen are from the 28 students in grade 20, some of them are already able to write essays coherently. Coherently means writing essays correctly, and other rules that are in accordance with the demands of learning to write essays. As for the habituation made by the teacher in improving students' writing skills in writing diaries, including instructing children to make a writing that tells memorable experiences for them in their diaries and instructing children to write down their daily activities both at home and at school into them diary.